Lies and Irony Understanding in Deaf and Hearing Adolescents. (1st June 2020) - González-Cuenca, Antonia; Linero, María José
Abstract: Lies and irony are paradigmatic examples of nonliteral communication; many deaf children and even adults have difficulty in understanding them. The present study assessed the understanding of lies and irony in 96 adolescents living in Spain in urban settings (58 deaf participants, 38 hearing participants; 10–19 years old). We investigated whether deaf and hearing participants differ in their performance, and the effects of age, theory of mind (ToM), and language on the understanding of these nonliteral meanings in deaf participants. The results show that deaf participants do not find it difficult to detect nonliteral statements, but they experience difficulty in attributing the real motivation to the speaker. ToM and language explained performance in the understanding of nonliteral communication in the deaf group. The results suggest the need to focus on promoting the ability to attribute real motivations to speakers. We propose an assessment sequence that differs from those used in other studies. In the proposed sequence, ToM skills would be combined with other skills that influence the understanding of lies and irony and would be sequenced according to the observed performance in deaf adolescents.